Stilistika dan Ideologi Hanada Taha Thomure dalam Pidato di TED Talks: ‘Al Lughah Al ‘Arabiyyah, Wathan’ - Khoirin Nikmah (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2022)
When it comes to public speaking, one of the keys to success is stylistics. In this case, the ability to play the stylistic aspect has an effect on the process of persuasion for the audience. This research paper is about Dr. Hanada Taha Thomure's TED Talk,